Is the holistic physical factor linked to life satisfaction in older age? - Boris Miha Kaučič; Marija Ovsenik; Bojana Filej (Nofer Institute of Occupational Medicine, 2019)
Background The physical factor (health literacy, health status, functional ability to perform daily basic and instrumental activities and risk factors) is linked to life satisfaction in older age. The aim of this study is to establish the correlation between the physical holistic factor and life satisfaction in older age. Material and Methods The quantitative research method was used. In order to sample the data, the authors chose a simple random sample. The designed questionnaire was filled in by 1064 older persons aged ≥ 65 years, living in social care institutions/nursing homes for older persons or in the home environment. The number of correctly completed survey questionnaires was 656. In order to measure life satisfaction, the Satisfaction with Life Scale was used. Within the physical factor, 4 indexes were formed. In order to be able to show the desired influences or links between the physical factor and life satisfaction, the authors used propensity score methods. Results The individual indexes within the physical factor are linked to life satisfaction to a varying degree: health literacy (R 2 = 0.137), health status (R 2 = 0.047), the functional ability to perform daily basic and instrumental activities (R 2 = 0.015), and risk factors (R 2 = 0.001). The physical holistic factor is linked to life satisfaction in older age (R 2 = 0.05). Conclusions With this research, the authors have proven that the older persons with high levels of health literacy, a good health status without chronic diseases, who are independent in performing daily basic and instrumental activities, and do not have any risk factors present, are more satisfied with their lives. Med Pr. 2019;70(5):535-43